Tests of Income Convergence in ASEAN and SAARC Trading Blocs. Issue 2 (September 2019) - Zia, Uzma; Mahmood, Zafar
The cherished goal of speedy economic growth in the Asian regional blocs cannot be achieved without attaining income convergence among them. Economic integration and assessment of income convergence or disparities among Asian blocs is the aim of this study. This study assesses a number of factors, such as trade openness, foreign direct investment, intellectual property rights protection and governance, to see how open economies are integrating themselves while competing with each other. Findings reveal that the SAARC group has not shown intra-regional income convergence, while the ASEAN group provides sufficient evidence. Although simultaneously considering SAARC and ASEAN groups in the form of a panel, there is evidence of non-convergence between the two regional groups. An important policy implication of the study is that the ASEAN and SAARC blocs are in dire need for combined and collective policy framework at the regional level. JEL: O19, O31, F15